Influence of water diversion system topologies and operation scenarios on the damping characteristics of hydropower units under ultra-low frequency oscillations. (15th January 2022) - Lu, Xueding; Li, Chaoshun; Liu, Dong; Zhu, Zhiwei; Tan, Xiaoqiang
Abstract: Ultra-low frequency oscillations are the typical dynamic stability problem of hydropower-dominated power systems. Hydraulic factors can directly affect hydropower unit damping, and related studies focus on the influence of hydraulic parameters on unit damping under a fixed operation situation, while ignoring the characteristics of water diversion system topologies (WDST) and diverse hydropower operation scenarios. In this paper, some simulation models of the hydro-turbine governing system (HTGS) with a variety of WDST are first established. Then, a damping calculation method based on phase diagrams is used to calculate the damping of overall system under different WDST and operation scenarios. The results show that the increase of the number of branch pipes in WDST will deteriorate the damping characteristics and setting a surge tank can effectively increase the damping. In addition, if there is a hydraulic connection between the unit integrated into a small power grid (SPG) and the unit integrated into a large power grid (LPG), the strong stability of the LPG will increase the damping of the unit integrated into SPG. Closing some units in multi-unit HTGS will improve damping characteristics of the running unit. Some measures to suppress ULFO are proposed from the perspective of design and stable operation. Highlights: A non-linear hydro-turbine governing system model with 18 types of water diversion systems is established. The effect of surge tanks and the number of branch pipes on damping is researched. The effects of grid-connection types and the number of running units on damping is clarified. Several strategies to suppress ultra-low frequency oscillations are proposed from the perspective of design and operation.